PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PKN MENGGUNAKAN MODEL KOOPERATIF TIPE TGT DI SEKOLAH - -, RAMADHANI (Universitas Negeri Padang, 2014)
This research was conducted due to the students low learning achievement in Civics in grade IV of SDN 07 Balingka. This was a Classroom Action Research which applied both qualitative and quantitative approaches. This research covered the activities of planning, acting, observing and reflecting. It was conducted in two cycles by applying TGT cooperative model. The subject of the research was the researcher and the students in grade IV. The results of the research indicated that from cycle I to cycle II : (1) the socre of the Lesson Plan improved from 81% to 97%, (2) the teacher’s activities increased from 85% to 97%, (3) the students’ activities improved from 85% to 96%, and (4) the students’ learning achievement increased from 68 to 80. Key Terms: Learning Achievement, Civics Learning, Teams Games Tournament (TGT) Learning Model